Twin - Peaks in E.U. Regional Productivity Dynamics: a nonparametric analysis - Georgios Fotopoulos (Max Planck Institute of Economics, 2005)
Working within the 'distributional approach', this research offers evidence, based on empirical density estimates and modality tests, of past polarization in regional labour productivity in EU-15. Most importantly, it provides evidence on the related ergodic density which suggests that this polarization may persist in the future. This past and probably future polarization is primarily related to the service sector of the regional economies and not to manufacturing industries sector.
Keywords: O18; D39; C14; 330; regional labour productivity; EU; distributional analysis; nonparametric methods; stochastic processes; Arbeitsproduktivität; Regionale Disparität; Dienstleistungssektor; Schätzung; EU-Staaten